Evaluating energy security efficiency in the EU transportation sector: A multi-stage efficiency analysis - Gokgoz, Fazil; Yalcin, Engin (Elsevier Sci Ltd, 2026)
In this study, energy security of the EU countries in transportation sector is evaluated. The first stage focuses on slack-based DEA. The second stage uses Stochastic Frontier Analysis (SFA) to investigate how various external environmental variables, namely GDP per capita, research and development expenditure, and level of urbanization, affect the EU countries' efficiency scores. Finally, the DEA efficiencies are recalculated to adjust for these environmental effects in order to allow for a more robust comparison of the EU countries. Bulgaria, Poland, and Hungary in the eastern EU exhibit notable inefficiencies after external adjustment whereas Germany, Denmark, and Sweden are on the efficiency frontier. Findings indicate an average efficiency declined from 0.86 in Stage 1 to 0.74 in Stage 3, suggesting 12 % decline is due to environmental circumstances as opposed to managerial efficacy. SFA findings indicate GDP per capita; R&D expenditures have a positive effect on efficiency, while urbanization had a negative effect, resulting from congestion and intensity of use for resources. This study aims to fill a research gap by employing a slack-based DEA and SFA in a multi-staged framework to examine the efficiency of energy security of the EU transportation sector, which indicates that clean energy transition is an effective pillar to increase efficiencies of countries and help organize transportation policies.
Keywords: Transportation; Energy security; Clean energy; Three-stage DEA; European union